Permissiveness on Trial: Sex, Drugs, Rock, the Rolling Stones, and the Sixties Counterculture. Issue 2 (15th March 2019) - Collins, Marcus
ABSTRACT: The Redlands Affair, which involved drug-taking by countercultural musicians, was the defining scandal of Britain's "Summer of Love". It catalyzed a debate about the nature and extent of the "permissive society" that continues to this day. This article analyzes the diverse and extensive sources generated by the Affair's principal participants  - the Rolling Stones, the press, the courts, politicians, and the counterculture  - to show how they clashed over what was and was not permissible in matters of personal conduct, individual liberty, and social responsibility. The provisional, contested, and circumscribed quality of permissiveness revealed by these debates has not been fully captured in previous accounts of the Affair or in broader narratives of the 1960s. Permissiveness was not a monolithic cause, and existing models of it  - whether they stress its marginality or its magnitude, its malign or benign effects  - risk simplifying a portmanteau concept encompassing a range of behaviors and beliefs championed by different interests for different reasons.